Association between Diet and Adiposity in Adults: Influence of Sedentary Behavior Patterns - Beretta, Victor Spiandor [UNESP]; Tebar, William Rodrigues; Scarabottolo, Catarina Covolo [UNESP]; Delfino, Leandro Dragueta [UNESP]; Saraiva, Bruna Thamyres Ciccotti [UNESP]; Santos, Amanda Barbosa [UNESP]; Antunes, Ewerton Pegorelli [UNESP]; Leoci, Isabella Cristina [UNESP]; Ferrari, Gerson; Christofaro, Diego Giulliano Destro [UNESP] (MDPI, 2023)
This study analyzed the influence of sedentary behavior (SB) on the association between dietary patterns and adiposity in community-dwelling adults. Eight hundred and forty-three adults (age: 56.5 ± 18.3 years) participated in this cross-sectional epidemiological study. Dietary patterns were evaluated using self-report questions regarding the weekly frequency of consumption of certain foods. Adiposity was determined using anthropometric measurements of weight, waist circumference, and height. SB was evaluated according to the time spent on screen devices. The usual physical activity level and socioeconomic status were considered confounding factors. Associations were determined using multivariate linear models with simultaneous adjustments for confounding variables. A statistical analysis indicated that fruit consumption was negatively related to the body mass index, regardless of the adjustment for SB domains. Red meat consumption was positively related to the body mass index, and fried food consumption was positively related to the waist-to-height ratio, regardless of the adjustment for SB domains. The consumption of fried food was positively associated with global and central adiposity after the adjustments for confounding factors and time spent on screen devices. We concluded that dietary habits are related to adiposity in adults. However, SB domains seem to influence the relationship between body adiposity and dietary habits, mainly regarding the consumption of fried foods.
Keywords: dietary pattern; epidemiology; nutrition; overweight; public health; sedentary behavior